Dietary Choices of a Foregut-Fermenting Primate, Colobus guereza: A Comprehensive Approach Including Leaf Chemical and Mechanical Properties, Digestibility and Abundance - Matsuda, Ikki; Hashimoto, Chie; Ihobe, Hiroshi; Yumoto, Takakazu; Baranga, Deborah; Clauss, Marcus; Hummel, Jürgen (Frontiers in Ecology and Evolution, 2022)
Free-ranging animals make dietary choices that affect their nutritional status and, ultimately, their health and fitness. We investigated food selection by a leaf-eating foregut-fermenting primate, the guereza (Colobus guereza), using multiple criteria, including chemical and mechanical properties, in vitro digestibility and leaf abundance, on the basis of 30 consecutive months of behavioural observations (4308 h in total) in the Kalinzu Forest, Uganda, as well as vegetation surveys. We noted that leaf toughness may be a proximate cue for the chemical properties of plant foods, especially for protein, which is an important selection factor used by foregut-fermenting primates. We also found that the in vitro digestibility of plant foods was greatly influenced by the concentrations of fibre and secondary compounds. At a broad level, none of the studied factors, including leaf chemical and mechanical properties, digestibility and abundance, affected whether guerezas consumed specific leaf items. At a more detailed level, however, protein content, digestibility and toughness were related to the percentage of foraging effort that guerezas devoted to specific items in our study site.